¹³⁷Cs circulation in forest eco systems on the territory of the Chornobyl exclusion zone (Plant) - Zarubina, N.Ye. (Доповіді НАН України, 2022)
Seasonal changes in the content of ¹³⁷Cs in plants of the forest ecosystems on the territory of the Chornobyl exclusion zone have been studied. Samples were selected from 2013 till 2015 once per two weeks. The studied objects were one- and two-year-old needles and branches of the Scots pine (P. sylvestris). The ¹³⁷Cs content was measured by the gamma spectrometry. In the needles and branches of P. sylvestris, the maximum values of ¹³⁷Cs concentration are noted in the summer. The minimum values of ¹³⁷Cs content in the studied organs of P. sylvestris are characteristic of the autumn-winter period. Probably, the annual fluctuations in the content of this radionuclide in various organs of the studied plants are a consequence of the existence of the constant circulation of ¹³⁷Cs in the forest ecosystems, as a result of which this radionuclide not only gets from the soil into P. sylvestris, but is also excreted from its living tissues.